Postgraduate Studies in PFUR in the context of Top Skills Professional Training for Innovative Russia - O V Andreeva (Vestnik RUDN. International Relations, 2009)
This article deals with the process of realization of the Concept of doctoral and postgraduate studies development at the Peoples' Friendship University of Russia. The author characterizes the first stage of university educational area formation.